Measures of fetal growth and preterm birth and risk of endometriosis and adenomyosis in adult life: a systematic review and meta‐analysis - Marie Brønd; Kjerstine Breintoft; Axel Forman; Tine Brink Henriksen; Cecilia Høst Ramlau‐Hansen; Dorte Rytter; Linn Håkonsen Arendt (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction Exposures in utero are suggested to play a role in the etiology of endometriosis and adenomyosis, although the current evidence is inconclusive. Knowledge about potential prenatal programming and early life exposures that may affect this risk is of high importance, to focus potential preventive strategies for the diseases already during pregnancy. The aim of this study was to review systematically the literature of the association between measures of fetal growth and preterm birth and endometriosis and adenomyosis in adult life. Material and methods A systematic review according to Preferred Reporting Items for Systematic Reviews and Meta‐analysis (PRISMA) guidelines and by search on PubMed and EMBASE was carried out. We included published case–control and cohort studies. We excluded studies without a reference group, eg case series, case reports as well as commentaries, letters and editorials. The quality of the studies was assessed using the Newcastle–Ottawa Scale. Meta‐analyses using a random‐effect inverse variance weighted model were performed. PROSPERO registration number is CRD42021249322. Results A total of 11 studies were included. In general, the quality scores of the studies were moderate. We found that the risk of endometriosis was 26% higher in women born with a birthweight <2.5 kg (pooled odds ratio [pOR] 1.26, 95% confidence interval [CI] 1.05–1.52) and 32% higher in women born preterm (pOR 1.32, 95% CI 1.01–1.72) than in the reference groups. The studies on adenomyosis pointed towards no association, but a meta‐analysis was unfeasible due to the small number of studies. Conclusions This systematic review and meta‐analysis found that low birthweight and being born preterm were associated with endometriosis in adult life, but the results must be interpreted cautiously. No solid conclusion could be made regarding adenomyosis due to a limited number of published studies, but the studies included found no association. The results support the hypothesis of a potential early programming effect of endometriosis. However, the body of evidence is sparse and this hypothesis needs to be investigated further.